PENYU DALAM KARYA SENI GRAFIS INTAGLIO PRINT - Indra Suryadi; Ariusmedi Ariusmedi (Universitas Negeri Padang, 2021)
Sea turtles (Chelonioidea) can be found in all oceans except for the polar regions. Sea turtles have a pair of front limbs as rower legs which make swimming easier. Althought it stays in the water for the rest of its life, it occasionally has to go on surface of the water to take a breath.Sea turtles, in this artwork aims to visualizes an expression of the writer's anxiety about the endangered turtle population. This artwork made by the intaglio print technique as one of the graphic art techniques. After various observations and long steps of work, these 10 artworks created and displayed namely : 1) Pemangsa, 2) Pencurian telur, 3) Ancaman, 4) Abnormal, 5) Harapan, 6) Terdampar, 7) Memakan plastik, 8) Korban, 9) Impian, 10) Terjerat. This is the result of sea turtles artwork which illustrates the writer's anxiety about the current phenomenon. Besides, this graphic work is expected to be a source of encouragement for other creators.Keywords: Sea Turtles, Graphic Art, Intaglio Print